The Influence of Leadership Style and Work Environment on The Performance of Employees in the West Seram District Office, West Seram Regency - Ryalno Stefano Noya; Venezia Thalia Metekohy (Komunitas Dosen Indonesia, 2025)
This study analyses the influence of leadership style and workplace conditions on the performance of employees at the West Seram Subdistrict Office in the West Seram Regency. The study population consisted of 36 employees, selected using saturation sampling. Data were collected via a Likert-type questionnaire to measure participants' perceptions of the variables under study: leadership style, workplace environment, and performance. Data analysis was performed using multiple linear regression with SPSS software to obtain a more comprehensive empirical view of the relationship between the variables. The results show that leadership style has a positive and significant influence on performance, and that a supportive workplace environment also contributes significantly to its improvement. Furthermore, these two variables play an important role in increasing the effectiveness of the office's operations within the subdistrict. These findings confirm that adaptive leadership, effective communication, and a supportive workplace environment are key factors in strengthening human resource performance in the local public sector.